Relationship between the strength and the acoustical properties of concrete blocks mixed with pofa to replace several percentages of cement content : an initial study / Abdul Wafi Razali and Seti Mariam Ayop - Abdul Wafi, Razali; Seti Mariam, Ayop (2012)
This paper is basically an initial study. The objectives of this research are to evaluate the concrete compressive strength using POFA as cement replacement and to evaluate the performance of concrete blocks using POFA in term of sound insulation. Generally, there are four different percentages of POFA replacement in concrete which are 2.5%, 5%, 7.5% and 10% respectively. For compressive strength test, the concrete are tested on 7, 14 and 28 days. The concrete mixture was designed according to British standard with water cement ratio of 0.45. This research reveals the usage of POFA in concrete mixture can improve the compressive strength test and acoustical properties specifically for sound insulation. But the usage of POFA in concrete mixture strictly must not exceed 10% as it will decrease the performance of the concrete strength.